Hydrocarbons in crystalline rocks - Petford, N.; McCaffrey, Ken (Geological Society special publication, 2003)
While oil and gas fields in crystalline basement are still discovered mostly by accident, as shown in this book, such reservoirs can be very prolific, especially if the basement rock is highly faulted or fractured. The chapters in this volume cover a diverse range of topics related broadly to the theme of hydrocarbons in crystalline rocks, and challenge explorationists' definition of basement rock, which needs to be less narrow and more responsive to new geological ideas.